A lobulated mass on the upper back with prominent vasculature: A giant basal cell carcinoma - Elysha M. Kolitz; Brian L. Scott; Travis Vandergriff; Melissa Mauskar (PAGEPress Publications, 2021)
Basal cell carcinoma (BCC) is characterized by slow but locally invasive growth. Although there is low metastatic potential, if not treated early, these skin cancers can lead to significant morbidity and mortality. In this case report, we present a man with a neglected BCC that developed into what is termed a giant BCC or one that is greater than 5 cm. This tumor was discovered only upon workup of orthostatic lightheadedness and iron deficiency anemia. Although rare, basal cell carcinoma must be included on the differential of a large cutaneous lesion and may be a source of significant blood loss.